Advanced Covalent Organic Frameworks for Multi‐Valent Metal Ion Batteries. Issue 6 (29th November 2022) - Luo, Xiao‐Xi; Wang, Xiao‐Tong; Ang, Edison Huixiang; Zhang, Kai‐Yang; Zhao, Xin‐Xin; Lü, Hong‐Yan; Wu, Xing‐Long
Abstract: Covalent organic frameworks (COFs) have received increased interest in recent years as an advanced class of materials. By virtue of the available monomers, multiple conformations and various linkages, COFs offer a wide range of opportunities for complex structural design and specific functional development of materials, which has facilitated the widespread application in many fields, including multi‐valent metal ion batteries (MVMIBs), described as the attractive candidate replacing lithium‐ion batteries (LIBs). With their robust skeletons, diverse pores, flexible structures and abundant functional groups, COFs are expected to help realize a high performance MVMIBs. In this review, we present an overview of COFs, describe advances in topology design and synthetic reactions, and study the application of COFs in MVMIBs, as well as discuss challenges and solutions in the preparation of COFs electrodes, in the hope of providing constructive insights into the future direction of COFs. Abstract : Covalent organic frameworks (COFs) offer an opportunity for complex structural design and specific functional development, facilitating, for example, the applications of multi‐valent metal ion batteries (Zn 2+, Mg 2+, Al 3+ ). This comprehensive review describes COF synthesis and applications, provides advances in topology design and synthetic reactions, surveys the application of COFs in multi‐valent ion batteries, discusses the key issues of COF electrodes, and predicts future applications.